Effects of arsenite stress on growth and proteome of Klebsiella pneumoniae - Daware, Vandana; Kesavan, Suresh K.; Patil, Rajendra; Natu, Arvind; Kumar, Ameeta; Kulkarni, Mahesh J.; Gade, Wasudeo N. (Journal of Biotechnology, 2012)
In the present study an arsenite, As(III), tolerating bacterium, MR4, was isolated from Mulla River Pune, India, capable of reducing arsenate to arsenite and identified as Klebsiella pneumoniae (HQ857583). Comparative proteomic analysis using two-dimensional gel electrophoresis (2-DGE) and matrix assisted laser desorption ionization-time of flight-time of flight (MALDI-TOF/ TOF) was used to monitor the proteins undergoing changes in expression levels under 2.5 mM As(III) stress. The 2-DGE proteome map has shown that 60 proteins were differentially expressed under As(III) stress, of which 39 proteins were successfully identified with a MASCOT score greater than 70 (p < 0.05). Among the identified proteins, membrane transport/ binding proteins, porins, and amino acid metabolism enzymes were down-regulated while stress responsive proteins and antioxidant enzymes were up-regulated. Proteins involved in carbohydrate metabolism, particularly those in pentose phosphate pathway were also up-regulated while those involved in pyruvate metabolism were down-regulated. However, proteins involved in glycolysis and tricarboxylic acid cycle showed a mixed regulation response. These findings provide new insights into the probable mechanisms by which K. pneumoniae (HQ857583) could be adapting to As(III) stress. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: (2-DGE); Arsenite stress; Klebsiella pneumoniae; MALDI-TOF-TOF; Two dimensional gel electrophoresis